Mengenal Tradisi Arabistika di Rusia - Jamaludin Z, Wan (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
ABSTRAK: Russian interested to the great tradition of science and civilization such as Byzantium and Arab as reffererencein building their scientifical tradition in any diciplines and fields of studies like astronomy, astrology, and medical.This assimilation process between Russian and Arab has persisted since 9th-17th, which constructed in three main resourcessuch as linguistics, literature, and history of Islamic culture or orientalism.